The Impact of Adopting International Accounting Standards on Taxation – A Theoretical Preview - Abdallah salah Hasan Alseikh; Murad Ali Ahmad Al-Zaqeba; Izlawanie Muhammad (Universal Publishers - Boca Raton, Florida, USA, 2024)
Indexed by ERA